Verbal violence in the child's family environment and the importance of the culture of children's literature in reducing it - al-Ghailani, Salem bin Mohammed bin Ali (Journal of Educational and Psychological Sciences, 2018)
The problem of the current study was the study of the issue of verbal violence in the child's family environment and the importance of the culture of children's literature in reducing it. The study aimed to identify the level of this violence and its relation to some independent variables such as age, gender, Educational Parent. The study has also been exposed to literature directed at children through literary literature, the extent to which violent expressions exist, and the extent to which these words contribute to the spread or reduction of violence among this group. The study tried to identify the origin of the problem and to find some solutions through the recommendations made.The current study belongs to descriptive studies based on the descriptive approach, which is actually applied through the social survey methodology in the sample, for a random sample of basic education students in the state of Seeb in Muscat Governorate - Sultanate of Oman. Where the researcher prepared a questionnaire that was presented to a group of arbitrators and was approved, and the paragraphs of this questionnaire consists of the number of (29) words. The researcher designed the scale himself, adopting in design and style Likert Scale. , The researcher relied on qualitative and quantitative analysis methods, and according to the design of this study and in line with its objectives and questions. Based on the scientific method used in the descriptive approach and the type and nature of field data, these data were collected, confirmed and coded, And analyzed by relying on the Statistical Package for Social Silences. The study found several important findings that confirmed the existence of practices of verbal violence against the child in his family environment. As evidenced by cultural literature directed at the child or so-called children's literature, that these writings play an important role in increasing or reducing this violence.Finally, the study presented recommendations for raising awareness in the family, and advocating for children in the literature to promote their writings in a spirit of tolerance, distance from violence and acceptance of others through their writings.
Keywords: linguistic violence; family environment; child; Sultanate of Oman